North Africa at the End of the Later Roman Empire - TOUIL , Imad (The Algerian Historical Journal, 2026)
The article addresses an important period in the history of ancient North Africa, namely the late phase of Roman occupation. During this time, the region underwent numerous changes that affected economic, social, political, and even religious life, due to the political and military circumstances faced by the Roman Empire throughout the 3rd and 4th centuries AD. These circumstances had repercussions on various Roman provinces, including North Africa. Through this study, we aim to understand the different conditions in North Africa at the end of Roman occupation and the extent to which the region was influenced by the circumstances in Rome.